#Naijaalltheway : evoking the naija spirit through Pepsi advertisement - Mogaji, Emmanuel, (SAGE Knowledge. Cases., 2019)
Advertisers use music in various ways to appeal to consumer emotions and promote their products. This case explores how Pepsi localised its marketing campaign in Nigeria by adopting a customised and bespoke song for an advertisement that went viral in June 2018. Created by Pepsi Nigeria in collaboration with local musicians, the song carries a lyrical power that Nigerians can relate to and evokes the Naija spirit--a colloquial term used to describe a people full of life, love, loyalty, and resilience. The song offers Nigerian consumers a sense of belonging while tapping into their national pride ahead of the World Cup. This regionally specific strategy is reflected in the motto of the marketing campaign--Naija all the way.